The Christian Funeral as Counter Witness - Long, Thomas G. (Interpretation, 2021)
The proliferation of unconventional death practices in North America, however innovative, is in part an expression of societal confusion about the nature of death and grief. If the church can recover the theological and liturgical fabric of funerals, reclaiming their main purpose as public confession rather than private pastoral care, Christian funerals can serve as a hopeful counter-witness to an uncertain culture.